Manipulation of fatty acids in the estuarine clam Meretrix casta (Gmelin, 1791) by supplementation with the microalgal diet, Isochrysis galbana - Jayasankar, Vidya; Kizhakudan, Joe K.; Margaret Muthu Rathinam, A.; Santhosi, I.; Rajendran, P.; Thiagu, R. (Indian Journal of Fisheries, 2012)
The present study evaluated the changes in fatty acid profile of the estuarine clam Meretrix casta, an important foodorganism used in the larval rearing of scyllarid lobsters, after supplementation with the microalgal species Isochrysis galbana.The uptake and assimilation of lipids from the microalgal feed were verified by gas chromatographic analysis of fatty acidsin the clam tissues after eight days of feeding with I. galbana. Increase in concentrations of polyunsaturated fatty acids(PUFA), in particular docosahexaenoic acid (DHA, C22:6n3) and C18:2n-6, was observed in clams supplemented withI. galbana. Changes in monounsaturated fatty acid (MUFA) composition were less marked and related to the increasingproportions of C18:1, after supplementation. Feeding with I. galbana also induced a decrease in the proportion of saturatedfatty acids, which was related to decrease in proportions of both C16:0 and C18:0. Although the fatty acid compositionshowed significant differences, the gross lipid content of the clam tissues did not seem to be excessively influenced by thealgal feeding. Tissues from clams supplemented with I. galbana are being evaluated as feed for sand lobster larval trials.